2019
DOI: 10.1038/s41419-019-1382-y
|View full text |Cite
|
Sign up to set email alerts
|

circTADA2As suppress breast cancer progression and metastasis via targeting miR-203a-3p/SOCS3 axis

Abstract: More and more evidence indicates that circular RNAs (circRNAs) have important roles in several diseases, especially in cancers. However, their involvement remains to be investigated in breast cancer. Through screening circRNA profile, we identified 235 differentially expressed circRNAs in breast cancer. Subsequently, we explored the clinical significance of two circTADA2As in a large cohort of triple-negative breast cancer (TNBC), and performed functional analysis of circTADA2A-E6 in vitro and in vivo to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(186 citation statements)
references
References 53 publications
3
183
0
Order By: Relevance
“…Moreover, circRNAs have been regarded as potential therapeutic targets in breast cancer [6]. Xu et al reported that circRNA transcriptional adaptor 2A (circTADA2A) inhibits cell proliferation, migration and invasion by regulating microRNA-203a-3p/suppressor of cytokine signaling 3 (SOCS3) axis in breast cancer [7]. Furthermore, Zhang et al suggested that circRNA has_ circ_0052112, generated from zinc finger 83, could promote cell migration and invasion by sponging microRNA-125a-5p in breast cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, circRNAs have been regarded as potential therapeutic targets in breast cancer [6]. Xu et al reported that circRNA transcriptional adaptor 2A (circTADA2A) inhibits cell proliferation, migration and invasion by regulating microRNA-203a-3p/suppressor of cytokine signaling 3 (SOCS3) axis in breast cancer [7]. Furthermore, Zhang et al suggested that circRNA has_ circ_0052112, generated from zinc finger 83, could promote cell migration and invasion by sponging microRNA-125a-5p in breast cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…miR‐760 downregulation promoted SOCS3 expression. Previous studies validated that SOCS3 expression is downregulated in cancer tissues, including pancreatic cancer, colorectal cancer, lung cancer, bladder cancer, and breast cancer . SOCS3 overexpression has an anti‐proliferative and anti‐metastatic effect in cancer .…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies validated that SOCS3 expression is downregulated in cancer tissues, including pancreatic cancer, colorectal cancer, lung cancer, bladder cancer, and breast cancer. [32][33][34][35][36] SOCS3 overexpression has an anti-proliferative and anti-metastatic effect in cancer. 37,38 Previous studies have found that when a cytokine or a growth factor binds to an intracellular receptor as a ligand, the receptor can form a heterodimer and phosphorylate the JAK kinase.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circTADA2A-E6 could sponge miR-203a-3p to reduce the expression of miR-203a-3p; thereby restoring the expression of suppressor of cytokine signaling 3 (SOCS3), a target gene of miR-203a-3p, resulting in suppressed the progression and metastasis of BC. 68 In addition, circKIF4A promoted proliferation and migration of triplenegative breast cancer (TNBC), cells by directly sponging miR-375 to relieve the suppression of KIF4A target gene. 69 Moreover, more circRNAs, such as circPLK1, circ-UBE2D2, circBMPR2, circ_0025202, circ_0103552, circ_0072309, circ_001783, involved in the occurrence and development of BC by acting as miRNA sponge have been reported.…”
Section: Breast Cancermentioning
confidence: 99%